Interpenetrating polymer networks based on cyanate ester and fluorinated ethynyl-terminated imide oligomers - Y. Wen; J. Yan; J. Liu; Z. Wang (eXPRESS Polymer Letters)
Highly soluble fluorinated ethynyl-terminated imide (FETI) oligomers were prepared via a conventional one-step method in m-cresol, using 4, 4′-(hexafluoroisopropylidene) diphthalic anhydride and 2, 2′-bis(trifluoromethyl) benzidine as the monomers, and ethynylphthalic anhydride as the end-capper; then interpenetrating polymer networks (IPN) were formulated from FETI oligomers and bisphenol A dicyanate ester (BADCy) through a solvent-free procedure, and their thermal, mechanical, and dielectric properties were fully characterized. The curing mechanism was studied by model reactions using nitrogen nuclear magnetic resonance. As evidenced by differential scanning calorimetry analysis and rheological measurements, the FETI/BADCy blends exhibited lower curing temperature and shorter gelation time in comparison with pure BADCy due to the catalytic effects of ethynyl and residue amic acid groups. The properties of IPNs were fully compared with those of polycyanurate, and the results revealed that the incorporation of FETI into cyanate ester resins could significantly improve the toughness, glass transition temperatures, mechanical and dielectric properties of the resultant IPNs.